Calcium and vitamin D: roles, interactions and nutritional programming for bone development - Ana Zastulka; Simona Clichici; Bogdan Culic; Nadina-Liana Pop; Cristian-Doru Olteanu; Cristian Delcea; Lavinia Ioana Sabău; Teodora Mocan (Balneo and PRM Research Journal)
The contributions of calcium and vitamin D in optimal bone development have been widely studied in the biomedical field, including in rodent models, utilizing reference diets. Additionally, studies have emphasized the interrelation between calcium, vitamin D and other hormones as it pertains to osseous tissue function, as well as the role that signaling pathways play in bone synthesis and resorption. Recently, it has been reported in literature that rodent diets consisting of lower amounts of either calcium or vitamin D than the reference diets may lead to favorable bone growth. This review will describe the properties of calcium and vitamin D, their roles on bone formation, their interactions with parathyroid hormone, osteocalcin and the function of bone signaling pathways. Additionally, this review will outline the components of rodent reference diets and suggest possible dietary modifications that ensure healthy bone development